Robust image watermarking using hessenberg decomposition and SVD with integer wavelet transform - Ernawan, Ferda; Ahmad, Hisyam; Adi, Prajanto Wahyu; Zuriani, Mustaffa; Mohd Faizal, Ab Razak (Institute of Electrical and Electronics Engineers Inc., 2023)
Preventing unauthorized use and distribution has grown more difficult as a result of the extensive usage of the internet and the simplicity of duplicating and distributing digital media. Watermarking has come to be recognized as a successful remedy for this issue. Image watermarking is the process of adding a distinctive identifier to an image so that it is hidden from view but can still be read to establish ownership. This research proposes Hessenberg Decomposition (HD) and Singular Value Decomposition (SVD) in the Integer Wavelet Transform (IWT) domain to achieve high robustness. The proposed method utilizes the HD feature of the image to enhance the robustness of the watermark against attacks, while the SVD technique is used to achieve high invisibility and security. The IWT domain is employed to make the watermarking process more efficient, leading to a faster and more reliable watermarking algorithm. The results of the experiments demonstrate that the proposed scheme provides a high level of robustness for preserving the ownership of multimedia content and resistant to various image processing attacks. The outcomes demonstrate that, in terms of robustness and invisibility, the suggested approach performs better than the existing watermarking schemes.